Interaction of Garcinia cambogia (Gaertn.) Desr. and Drugs as a Possible Mechanism of Liver Injury: The Case of Montelukast - Silvia Di Giacomo; Antonella Di Sotto; Ester Percaccio; Erica Scuotto; Cecilia Battistelli; Gabriela Mazzanti; Francesca Menniti-Ippolito; Ilaria Ippoliti (Antioxidants, 2023)
Overweight and obesity prevalence has increased worldwide. Apart from conventional approaches, people also resort to botanical supplements for reducing body weight, although several adverse events have been associated with these products. In this context, the present study aimed at evaluating the toxicity of Garcinia cambogia-based products and shedding light on the mechanisms involved. The suspected hepatotoxic reactions related to G. cambogia-containing products collected within the Italian Phytovigilance System (IPS) were examined. Then, an in vitro study was performed to evaluate the possible mechanisms responsible for the liver toxicity, focusing on the modulation of oxidative stress and Nrf2 expression. From March 2002 to March 2022, the IPS collected eight reports of hepatic adverse reactions related to G. cambogia, which exclusively involved women and were mostly severe. The causality assessment was probable in three cases, while it was possible in five. In the in vitro experiments, a low cytotoxicity of G. cambogia was observed. However, its combination with montelukast greatly reduced cell viability, increased the intracellular ROS levels, and affected the cytoplasmic Nrf2 expression, thus suggesting an impairment of the antioxidant and cytoprotective defenses. Overall, our results support the safety concerns about G. cambogia-containing supplements and shed light on the possible mechanisms underpinning its hepatotoxicity.